Integrative management of recurrent anterior shoulder dislocation - Dasari Sri Lakshmi (Wolters Kluwer Medknow Publications, 2021)
Introduction: Shoulder joint is the most mobile ball and socket joint. It allows movement along three planes due to its bony configuration and loose joint capsule. Stability of shoulder joint mainly depends on muscle strength supporting the joint. Shoulder dislocation is common injury; anterior dislocation being most common. Main Clinical Findings and Diagnosis: 38 year male patient with a history of fourth recurrent anterior shoulder dislocation (RASD) reduced under anaesthesia was immobilized in sling for 6 weeks. After immobilization, active assisted flexion and abduction was restricted to 90° associated with pain and feeling of instability. Interventions: Integrative treatments of Ayurveda and Physiotherapy were given in three divided sessions, 7 days in each session for a total of 21 treatment days. Ayurveda treatments included Sthanika abhyanga (SA) and Shashtika shali pinda sweda (SSPS). Physiotherapy treatments included interferential therapy (IFT) and exercises. Outcome: Nourishing external treatments enhanced muscle strength and joint mobility. Conclusion: There was appreciable improvement in shoulder muscle strength, active range of motion (AROM) and no incidence of recurrence since past 2 years. The patient is able to carry out unhindered daily activities with full and free AROM.